Inflammation, a Double-Edge Sword for Cancer and Other Age-Related Diseases - Gupta, Subash Chandra; Kunnumakkara, Ajaikumar B.; Aggarwal, Sadhna; Aggarwal, Bharat B. (Frontiers in Immunology, 2018)
Increasing evidence from diverse sources during the past several years has indicated that long-term, low level, chronic inflammation mediates several chronic diseases including cancer, arthritis, obesity, diabetes, cardiovascular diseases and neurological diseases. The inflammatory molecules and transcription factors such as adhesion molecules, AP-1, chemokines, C-reactive protein (CRP), cyclooxygenase (COX)-2, interleukins (ILs), 5-lipooxygenase (5-LOX), matrix metalloproteinases (MMPs), nuclear factor (NF)-kB, signal transducer and activator of transcription 3 (STAT3), tumor necrosis factor (TNF), and vascular endothelial growth factor (VEGF) are molecular links between inflammation and chronic diseases. Thus, suppression of inflammatory molecules could be potential strategy for the prevention and therapy of chronic diseases. The currently available drugs against chronic diseases are highly expensive, minimally effective and produce several side effects when taken for long period of time. The focus of this review is to discuss the potential of nutraceuticals derived from “Mother Nature” such as apigenin, catechins, curcumin, ellagic acid, emodin, epigallocatechin gallate, escin, fisetin, flavopiridol, genistein, isoliquiritigenin, kaempferol, mangostin, morin, myricetin, naringenin, resveratrol, silymarin, vitexin, and xanthohumol in suppression of these inflammatory pathways. Thus, these nutraceuticals offer potential in preventing or delaying the onset of chronic diseases. We provide evidence for the potential of these nutraceuticals from pre-clinical and clinical studies.